2014
DOI: 10.1166/jbn.2014.1957
|View full text |Cite
|
Sign up to set email alerts
|

Galactoxyloglucan-Modified Nanocarriers of Doxorubicin for Improved Tumor-Targeted Drug Delivery with Minimal Toxicity

Abstract: Doxorubicin (Dox) is commonly used to treat human malignancies, and the efficacy of Dox can be maximized by limiting toxicity when combined with nanoparticles. PST-Dox nanoparticles were prepared via conjugation of doxorubicin to galactoxyloglucan polysaccharide (PST001) isolated from Tamarindus indica (Ti), and by ionic gelation with tripolyphosphate (TPP). This formulation possessed superior therapeutic efficiency because of the small size and increased surface-tovolume ratio. The PST-Dox nanoparticles exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…Spectral analysis indicated that PST001 retained its identity, even after combining with the drug moiety Dox, and there occurred inter-molecular interactions between PST001 and Dox during the formation of the PST-Dox nanoparticles. The FTIR spectra obtained was similar to what we recently published [19], indicating there were no significant variations even on long-term storage (Supplementary Fig. 1).…”
Section: Synthesis and Characterization Of Pst-dox Nanoparticlessupporting
confidence: 87%
See 3 more Smart Citations
“…Spectral analysis indicated that PST001 retained its identity, even after combining with the drug moiety Dox, and there occurred inter-molecular interactions between PST001 and Dox during the formation of the PST-Dox nanoparticles. The FTIR spectra obtained was similar to what we recently published [19], indicating there were no significant variations even on long-term storage (Supplementary Fig. 1).…”
Section: Synthesis and Characterization Of Pst-dox Nanoparticlessupporting
confidence: 87%
“…1G). Our published studies demonstrated that PST-Dox nanoparticles (10 nm) had a Dox encapsulation efficiency of 70% [19]. The high Dox content in the nanoparticles may in turn increase the efficiency of the treatment at the targeted sites.…”
Section: Synthesis and Characterization Of Pst-dox Nanoparticlesmentioning
confidence: 94%
See 2 more Smart Citations
“…The results for the free DOX group could be related to the previously reported toxicities that cause weight loss in mice, such as cardiotoxicity, neurotoxicity and nephrotoxicity. [45][46][47] Unlike the control and free DOX groups, the enhanced anticancer effects and reduced toxicities from application of the nGO@DOX-cPEG flakes (Supplementary Figure S8) led to accumulation and efficient delivery of DOX to tumor sites, which may be due to the sustained release and prolonged circulation in the bloodstream and the enhanced permeation and retention effect. 47,48 In addition, histopathological and immunohistochemical analyses were performed on the tumor masses to determine the expression levels of caspase-3, PARP, CD31 and Ki-67 (Figure 7c; Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%